The Internet as a determining factor in economic convergence across countries - Perez-Trujillo, Manuel; Lufin, Marcelo; Lacalle-Calderon, Maricruz (Technological and Economic Development of Economy, 2022)
This paper examines whether the Internet is a determining factor in explaining economic growth and convergence across countries when it acts as a channel of information and knowledge diffusion. Literature has identified around 140 possible growth factors, therefore given the contradictory results obtained from previous empirical studies it is crucial we understand the actual role of the Internet. Using the conditional convergence theory and a Bayesian panel data model averaging method from a sample of 100 countries between 1994 and 2017, our results demonstrate that an increase in access to the Internet is a non-determinant factor in economic convergence, being its probability of inclusion in the true growth model conditioned by the regressors included in the estimates and the time span analysed.First published online 25 November 2021